Germinação de sementes de atemoia (Annona Cherimola Mill. x A. squamosa L.) cv 'Gefner' submetidas a tratamentos com ácido Giberélico (GA3) e ethephon - De Oliveira, Marcos Campos; Ferreira, Gisela [UNESP]; Guimaraes, Vandeir Francisco; Dias, Glaucia Bravo (Soc Brasileira Fruticultura, 2010)
The aim of this work was to evaluate the effect of gibberellic acid (GA(3)) and ethephon, besides the interaction of both plant growth regulators, on the germinative process of atemoya seeds (Annona cherimola Mill. X A. squamosa L.), cultivar 'Gefner'. Experimental design was completely randomized, in a 5(2) factorial arrangement; treatments consisted of the combination among five GA3 (gibberellic acid) and five ethephon concentrations, totaling 25 treatments, with four replicates of 25 seeds per plot. GA3 concentrations were 0, 250, 500, 750, and 1000 mg L-1 i.a., whereas those of ethephon were 0, 25, 50, 75, and 100 mg L-1 i.a. Seeds were treated with both plant growth regulators through immersion in the different solutions for 36 h. Then, seeds were sown onto germitest paper roll and allowed to germinate in a germination chamber, in the dark and under 20 degrees C/8h-30 degrees C/16h alternate temperature. Germination percentage, time and speed index; normal seedling percentage; and dormant seed percentage were evaluated. There was an interaction of both plant growth regulators on the germinative process of atemoya seeds, which indicates that the germination percentage of atemoya seeds (Annona cherimola Mill. X A. squamosa L.), cultivar 'Gefner', increases by using 778 mg L GA(3), whereas the association among high GA(3) concentrations and 75-100 mg L-1 ethephon increases the germination speed index and the percentage of normal seedlings.
Germination of atemoya seeds (Annona cherimola Mill. x A. squamosa L.) gefner subjected to treatments with gibberellic acid (GA(3)) and ethephon
Keywords: plant growth regulators; propagation; Annonaceae; dormancy